Clínica e beatitude - Almeida, Bruno Vasconcelos de (2010)
This dissertation aims at problematizing a set of issues in contemporary subjectivation using literature, namely novels and some short stories, with a view to mapping ways of life and existence in the becomings of a given therapeutic attention. The set of issues encompasses the idea of vitality in every approached therapy, production of ways of life in literature and in therapy, paces of speed and slowness and the concept of process as material elements of the therapeutic undertaking, the processes of subject production carried about in the context of contemporary machines and, finally, beatitude. The concept of beatitude has been taken from a conceptual axis that runs through the thinking of Espinosa, Nietzsche, and Deleuze. The link between beatitude and psychotherapy refers back to the experimentation of a therapy s intensity edges, to the difficulties therein and to the limits that impose its end and consummation. The therapeutic procedure, as much as literature as therapeutic activity, may compose plans to produce healthier states able to favor encounters, try the intense, multiply the active energies, release happenings and becomings. It is about grasping life when it is collapse, hard and troublesome, when life and death are mutually potentialized. The work still has a second set of issues that aims at strengthening the first one: voice, listening, poetic conception of individuation, literary machines, utility of literature, singular essences, therapeutic variations. The writing of the dissertation operated in flows, cuts, disturbances, and problems stemming from the therapeutic work and the exercise of reading. Both constitute experimental practices and justify the cartographic and extracting procedures. Psychotherapy and Beatitude is the outcome of immersions in the sensitive field that cuts across the relations of resonance and difference between therapy and literature, and aims at contributing in the formation of a fruitful thinking for contemporary therapeutic issues